Analysis of Online Marketing Strategies Post Pandemic COVID-19 - Destina Paningrum; Andry Mochammad Ramdan; Tri Febrina Melinda; Okta Karneli; Tito Irwanto (PT Mattawang Mediatama Solution, 2023)
This research examines the analysis of marketing strategies carried out online after the COVID-19 pandemic. The research used in this research is descriptive qualitative research. Various sources were processed in this study such as books, research results, journals, and research articles. This research explains that the challenges and opportunities for business marketing that rely on digital applications during a pandemic are felt to be very diverse and complex. Post-covid-19 shopping behavior has changed based on the relationship between technology & culture. The pattern of spending on basic needs and shopping has changed due to the ease of using the internet for shopping and the existence of online services. Digital-based marketing for a profitable and sustainable business is proven to face many challenges and opportunities. The problem is that not all business people and customers understand and can apply technology, while the opportunity is that digital technology applications can innovate business marketing efforts efficiently, effectively, and productively. In addition, the role of digital marketing on the financial performance of several organizations and the implicit digital transformation model has been identified as the most important aspects related to the current COVID-19 situation.